A Mini-Review: Newtonian And Non-Newtonian Approximation To Polymer Melt Viscosity - Nur Aini Fauziyah (Lontar Physics Today, 2022)
Polymer viscosity is an important thing to study in rheology. Empirical and mathematical approaches must be carried out to determine the mechanism that occurs in the polymer when it enters the melting zone. We know that polymers are non-Newtonian materials when they enter the melting transition region. However, another unique characteristic related to the viscosity of the polymer makes the polymer a superior material according to its application. Therefore, in this paper, we will briefly review Newtonian and non-Newtonian approaches to polymer viscosity. Maybe this paper can help become a reference for further applications in materials that have flowing properties.Keywords: polymer, viscosity, non-Newtonian, Newtonian